Characterization of protease from alkali-tolerant bacillus Sp. Ds2 isolated from lonar soda lake, india - VIJAYSHREE M. HEMKE; VISHAL R. DHUNDALE (International Journal of Pharma and Bio Sciences, 2017)
The among several strains of moderately alkalophilic bacteria that were isolated from Lonar lake, Bacillus sp. DS2 was selected as the best producer of extracellular protease and was used for further studies. Phenotypic and biochemical classiï¬cation analysis placed DS2 in the genus Bacillus. The bacterium was Gram positive, aerobic, motile, sporulating and rod-shaped bacterium and optimal growth temperature was found to be 37°C. The cells were able to grow well at a pH range of 8-10 which indicate that Bacillus sp DS2 was alkalophilic. The protease exhibited its optimal activity at 90°C and optimum pH 10.5. The enzyme activity was enhanced by Ethanol, Methanol, Chloroform, Benzene, Hexane, Propanol, Acetone, Xylene and Acetic acid. However, the protease activity was inhibited by Ethyl acetate. The optimum protease activity was enhanced in presence Chloroform (208.07%). The enzyme activity has enhanced by FeCl3, BaCl2 and CaCl2 and optimum enzyme activity enhanced by MgCl2 indicating it was a metalloenzyme with a potential to be a candidate for the biotechnological potential.